Palm oil clinkers as composite materials in marshall mix design - Nor Azrini, Musa (2012)
Palm oil industry becomes one of the main Malaysian commodities as indicated in Ninth Malaysian Plan (RMK9). As Malaysian focus on biotechnology industry, it is expected that million tons of waste produced annually and treated as disposal waste. By recycle the waste, it is not only can save the disposal area but also can sustain green environment. The Economic growth has led to the rapid increase of the demands for the aggregate for use in civil engineering field. The roads are the main links for all type of transportation to travel from one to another place. The growth of economy in a country also depends to the system of roads of the country itself. Besides, the decreasing of natural aggregate in our country is turning out to be a problem as its important for future generation. Since the road construction in Malaysia really developing rapidly and costs a lot in a project, an alternatives method or material need to been identified to minimize the cost and gives a good quality of pavement for long term usage. Malaysia also produce a large volume of palm oil waste and the usage of palm oil clinker in hot mix asphalt will make benefits for the environment and solid waste management. Malaysia is known as main manufacturers of palm oil in Asian region. Every oil mill produces a waste byproduct, known as clinker. Clinker was found to be suitable to replace normal gravel aggregate in concrete mixture and also mix design for pavement. For this project, palm oil clinkers will be mix together with the natural aggregate in Hot Mix Asphalt with different composition. The proportion for each category varies as Sample A contains 90% Natural Aggregate and 10% Palm Oil Clinker, Sample B contains 80% Natural Aggregate and 20% Palm Oil Clinker, Sample C contains 70% Natural Aggregate and 30% Palm Oil Clinker. From the experiment, the values of LA Abrasion for natural aggregate and palm oil clinker are 34.4% and 47%. This value will be compared with the JKR Standard which specifies the value for LA Abrasion should be less than 60%.The aggregate impact Value for natural aggregate is 16.62% and for palm oil clinker is 18.08%. JKR requirement For AIV Test is Not Exceed 30%.